A novel compact dual‐band circular/linear polarization switchable slot annular antenna with filtering network. Issue 9 (4th June 2021) - Cui, Jingyu; Zhang, Anxue; Yan, Sen
Abstract: A novel compact dual‐band circular/linear polarization (CP/LP) switchable slot annular antenna with integrated filtering network is proposed in this paper. The feed network is composed of a couple of stepped impedance resonators (SIR) with favorable dual‐band filtering characteristic. The SIR structure loaded with T‐shape branches can adjust the center frequency more flexibly especially for dual band operating. A PIN diode is welded on the slot antenna to achieve the transform between the linear polarization and the circular polarization of the filtering antenna. The proposed dual‐band CP antenna easily achieves 10 dB impedance bandwidth of 140/180 MHz and 3‐dB axial‐ratio bandwidth approximating 230/210 MHz at 2.6/4.8 GHz.